Transgenerational inheritance of modified DNA methylation patterns and enhanced tolerance induced by heavy metal stress in rice (Oryza sativa L.). - Xiufang Ou (Public Library of Science (PLoS), 2012)
Background DNA methylation is sensitive and responsive to stressful environmental conditions. Nonetheless, the extent to which condition-induced somatic methylation modifications can impose transgenerational effects remains to be fully understood. Even less is known about the biological relevance of the induced epigenetic changes for potentially altered well-being of the organismal progenies regarding adaptation to the specific condition their progenitors experienced. Methodology/principal findings We analyzed DNA methylation pattern by gel-blotting at genomic loci representing transposable elements and protein-coding genes in leaf-tissue of heavy metal-treated rice (Oryza sativa) plants (S0), and its three successive organismal generations. We assessed expression of putative genes involved in establishing and/or maintaining DNA methylation patterns by reverse transcription (RT)-PCR. We measured growth of the stressed plants and their unstressed progenies vs. the control plants. We found (1) relative to control, DNA methylation patterns were modified in leaf-tissue of the immediately treated plants, and the modifications were exclusively confined to CHG hypomethylation; (2) the CHG-demethylated states were heritable via both maternal and paternal germline, albeit often accompanying further hypomethylation; (3) altered expression of genes encoding for DNA methyltransferases, DNA glycosylase and SWI/SNF chromatin remodeling factor (DDM1) were induced by the stress; (4) progenies of the stressed plants exhibited enhanced tolerance to the same stress their progenitor experienced, and this transgenerational inheritance of the effect of condition accompanying heritability of modified methylation patterns. Conclusions/significance Our findings suggest that stressful environmental condition can produce transgenerational epigenetic modifications. Progenies of stressed plants may develop enhanced adaptability to the condition, and this acquired trait is inheritable and accord with transmission of the epigenetic modifications. We suggest that environmental induction of heritable modifications in DNA methylation provides a plausible molecular underpinning for the still contentious paradigm of inheritance of acquired traits originally put forward by Jean-Baptiste Lamarck more than 200 years ago.